Enhancement of Low pH Stress Tolerance in Anthocyanin-Enriched Transgenic Petunia Overexpressing RsMYB1 Gene - Naing, Aung H.; Lee, Deuk B.; Ai, Trinh N.; Lim, Ki B.; Kim, Chang K. (Frontiers in Plant Science, 2018)
We investigated whether the presence of anthocyanins in plants could contribute to low pH stress tolerance using anthocyanin-enriched transgenic petunia lines (PM2 and PM6) expressing RsMYB1 and WT plants. We examined several physiological and biochemical factors and the transcript levels of genes involved in abiotic stress tolerance. A reduction in plant growth such as plant height and fresh weight was observed when plants (PM2, PM6, and WT) were exposed to low pH (pH 3.0) condition when compared to the growth at normal (pH 5.8) condition. Less reduction in the growth of PM6 was observed, followed by PM2 and WT, which reflects the anthocyanin levels in the plants (PM6 >PM2 >WT). Analysis of physiological and biochemical factors also supports the degree of low pH tolerance in the plants (PM6 >PM2 >WT). In addition, enhanced expression of the genes (SOD, CAT, POX, and Osmotin) was observed in the transgenic lines (PM2 and PM6). The resultant of the enhanced transcript levels of the genes might promote antioxidant activities and proline content involved in the mechanisms underlying abiotic stress tolerance in plants. These results suggest that anthocyanin-enriched plants overexpressing RsMYB1 enhances low pH stress tolerance by elevating transcript levels of antioxidant- and proline-related genes.